BEER BARRELS FROM TEL GOREN, EIN GEDI - Hadas, Gideon (Revue biblique, 2004)
Prof. Mazar revealed many big clay barrels in Tel goren, Ein Gedi, Israel. He suggested that the barrels were part of workshops for perfume production industry during the First Temple Period. I suggest that these barrels were used as barley silos connecting with bear production. Barley was the staple grain food in the Dead Sea region. Le professeur B. Mazar a mis au jour de nombreuses grandes jarres en céramique, en forme de tonneaux, au Tel Goren (Aïn Gedi). Il supposait que ces jarres appartenaient à des ateliers de parfumerie, de l'époque du Fer II. Je propose que ces « tonneaux » soient des silos à orge, destinés à la production de bière. L'orge était l'aliment de base dans la région de la mer Morte.